YEŞİL TEDARİKÇİ SEÇİMİNDE BULANIK ÇOK AMAÇLI DOĞRUSAL PROGRAMLAMA YAKLAŞIMLARININKARŞILAŞTIRILMASI. - ÇALIK, Ahmet (Electronic Turkish Studies)
One of the main issues to be addressed in supply chain management is the supplier selection which aims to deliver the right product at the right time, in the right quality, in the right place, and at the most appropriate cost. Enterprises that select the right suppliers and determine the appropriate order distribution are more competitive in terms of competitiveness than others because the performance of suppliers, such as cost, quality, on-time delivery, and flexibility, affects direct production in achieving their goals. Legal regulations and increasing awareness among people about the protection of the environment has forced companies to attach importance to Green Supply Chain Management (GSCM) practices which have led to the concept of Green Supplier Selection (GSS) in supplier selection. GSS is a Multi- Criteria Decision Making (MCDM) problem involving qualitative and quantitative conflicting factors. Many individual and integrated approaches for GSS have been proposed and continue to be proposed. Several approaches have been proposed to convert multi-objective linear programming problems, which involve multiple conflicting objectives, to a single-objective linear programming problem. In this study, a new Multi-Objective Linear Programming (MOLP) model was for GSS. Fuzzy Multi-Objective Linear Programming (FMOLP) approaches, which are frequently used in the literature, are discussed in order to convert the developed MOLP to the single-objective linear programming problem. A comparison of solution approaches has been made in order to choose the best supplier and to make order allocation. In addition, the Analytical Hierarchy Process (AHP) method was used to determine the weights of the determined criteria in order to measure the influence of decisionmakers' opinions on the model. The feasibility and comparability of the proposed model and the FMOLP approaches are illustrated with an example.